Die opkoms en huidige stand van die Nuwe-Testamentiese ondersoek in Suid-Afrika: Deel 1 - Toit, Andries Bernardus du (Hervormde teologiese studies, 1993)
The rise and current state of New Testament research in South Africa In the first part of this presentation the ground-breaking contributions of John William Colenso and Johannes du Plessis are summarily characterized, as well as the pioneering role of EP Groenewald, WJ Snyman and AS Geyser.